Barriers to positive bystander behavior: understanding undergraduate physical education students’ attitudes and intentional behavior in gender-based violence prevention - Tiphaine Clerincx; Hebe Schaillée; Inge Derom (Frontiers in Sports and Active Living)
IntroductionGender-based violence (GBV) is a global issue that is reported in multiple contexts, including higher education institutes (HEI) and sports settings. Individuals whose gender identity or gender expression diverges from the dominant norms within sports or HEIs are at an increased risk of experiencing GBV. Gender-based violence is broadly defined as any form of interpersonal violence directed at individuals based on their gender identity or gender expression. Undergraduate physical education (PE) students are uniquely positioned to act as change agents in the prevention of GBV, given their connection to both education and their ambition to become professionals in the sport sector. The aim of this study is to investigate PE students’ perceptions of GBV, their attitudes, and intentional bystander behavior when witnessing GBV.MethodsAn explorative qualitative research design using focus groups was conducted in Spain and Belgium and involved 65 undergraduate PE students selected through convenience sampling from 5 HEIs, 41 identified as males and 24 identified as females. Data were gathered through 9 focus groups guided by a semi-structured interview guide and subsequently analyzed via Nvivo through reflective thematic analysis.ResultsStudents perceived GBV as psychological, physical, and sexual violence directed at individuals based on their sex or gender identity. Their perceptions of GBV prevention were shaped by social norms and generational differences. Key barriers to intervening in GBV situations included societal norms, a lack of competencies, and the natural stress response PE students experienced when witnessing GBV.DiscussionThe findings of this study underscore the need to shift GBV prevention interventions from merely raising awareness and disseminating knowledge to equipping PE students with skills in stress management and self-regulation. These insights lay the groundwork for developing more effective, context-sensitive GBV prevention interventions within HEIs.